A RNA producing DNA hydrogel as a platform for a high performance RNA interference system - Jaejung Song (Nature Portfolio, 2018)
Interfering RNA have a range of therapeutic and research based applications, issues with delivery have made systems that make siRNA in situ of interest. Here, the author report on the creation of a DNA hydrogel with improved stability and transcription efficiency over plasmid DNA.